Hearing loss and executive functions – results from a population-based cohort study - Julia Döge; Daniëlle Otten; Berit Hackenberg; Karoline O’Brien; Manfred E. Beutel; Isabel Heinrich; Jörn M. Schattenberg; Stavros V. Konstantinides; Thomas Münzel; Karl J. Lackner; Irene Schmidtmann; Julian Chalabi; et al. (PLoS ONE, 2026)
Introduction Hearing loss is linked to cognitive decline, yet its relation to specific executive functions remains unclear. This study examines associations between planning ability, pure-tone audiometry and speech-in-noise performance. Methods Data were drawn from the Gutenberg Health Study (GHS), a large population-based cohort at the University Medical Center Mainz. Participants with complete pure-tone audiometry and planning ability data were included ( N = 4,458; 2,314 males (51.9%), 2,144 (48.1%) females; mean age 58.0 ± 10.1 years, range 40–80). Audiologic testing included air- and bone-conduction pure-tone audiometry; hearing impairment was defined by WHO threshold. Speech-in-noise perception was measured using the German Matrix Test “Oldenburg Satztest”. Planning ability was assessed using the Freiburg version of the Tower of London. Associations were analyzed with linear and logistic regression. Results Hearing loss (HL ≥ 20 dB; both ears) revealed a significant negative association with planning ability total score (β = −0.346, p < 0.01), but not significantly with clinical executive dysfunction (<16. Percentile total TOL) (OR=1.109, p = 0.43). Higher planning ability reduced the likelihood of hearing impairment (OR=0.97, p = 0.006) and was linked to better speech-in-noise perception (lower OLSA SRT, β = −0.035, p = 0.001). Conclusion Hearing loss is linked to reduced planning ability, while higher planning ability decreases the likelihood of hearing impairment and increased speech perception in noise. These findings support models proposing that hearing loss imposes additional demands on working memory and attention. Longitudinal studies are needed to clarify causal directions and the potential role of interventions.